ANALISIS PROSEDUR DAN KEBIJAKAN KREDIT UNTUK MEMPERKECIL RESIKO KERUGIAN PIUTANG TAK TERTAGIH (Studi kasus pada PT. Federal International Finance Cabang Sukabumi) - Putri, Rahita Rosdiana; Nugroho, Gatot Wahyu; Kartini, Tina (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to determine the credit procedures and policies carried out by PT. Federal International Finance (FIF) Sukabumi Branch. The methodology used in this research is descriptive analysis with a qualitative approach. The data used in this study are primary and secondary data and data collected through observation, interviews and documentation, and literature study data analysis methodology used is analysis before the field and analysis during and after the field by means of data reduction, data display (data presentation ) as well as drawing conclusions and verification.